Real-world outcomes of metastatic cancer patients hospitalized at initial diagnosis: ONIRIS, a national study - Vercueil, Colin; Varnier, Romain; Seban, Romain; Ciaptacz, Lisa; Pavillet, Julien; Fraisse, Cléa; Darbas, Tiffany; Abdallahoui, Safa; Cox, David; Martin, Sophie; Trensz, Philippe; Kurtz, Jean-Emmanuel; et al. (Supportive care in cancer, 2025)
Purpose Therapeutic management of metastatic cancer patients who are hospitalized at the time of initial diagnosis because of impaired performance status and/or severe symptoms is challenging for clinicians. This study aims to describe their outcome. Methods In this prospective multicentric study, we included all adult, inpatients with newly diagnosed metastatic solid tumors between November 2021 and May 2022. Patients were followed for 3 months.. Our primary objective was to describe overall survival (OS). Secondary objectives included assessing SANT effectiveness in specific subgroups, identifying baseline factors associated with SANT initiation, and assessing usual prognostic tools and factors associated with response. Results 107 patients were included. Seventy-four (69%) initiated a SANT. Among them, 39 patients were alive at 3 months. Median overall survival was 1.7 months for the entire cohort. Thirty-seven patients (55%) died in the unit where they were first admitted. Patients with chemo-sensitive tumors, such as testicular non-seminomatous germ cell tumors (100% OS at 3 months), or those receiving targeted therapies or hormone therapies (80% OS at 3 months), showed numerically better outcomes. Factors associated with the initiation of a SANT were young age (OR = 0,94 [0,90; 0,98]), low Charlson Comorbidity Index (OR = 0,56 [0,42; 0,73]), and patient’s or caregiver’s request for treatment (respectively, OR = 0,07 [0,02; 0,17] and 0,17 [0,06; 0,42], compared to the respective reference category (no request)). Conclusion Metastatic cancer patients hospitalized at the time of diagnosis share a similar poor survival. Despite the notable exception of chemo-sensitive tumors and specific molecular alterations, the high mortality observed in both groups suggests that SANT has a limited impact on their outcomes. Best supportive care can be reasonably considered for these patients. The benefit of SANT in this altered population should be assessed in larger prospective studies.